Design Thinking Model for Digitalizing Information Systems in Indonesia–Timor Leste Border Vocational Schools - Krisantus Jumarto Tey Seran; Hevi Herlina Ullu; Ernes Josias Blegur; Nila Puspita Sari (SISTEMASI, 2026)
SMK Suarna Wisata Tes is located along the border area between Indonesia and Timor-Leste. As part of Indonesia’s 3T region (Tertinggal, Terdepan, dan Terluar — disadvantaged, frontier, and outermost areas), the school represents the progress of Indonesian education in neighboring border communities, particularly for the people of the Oecusse District. One of the main limitations faced by SMK Suarna Wisata Tes is the absence of a centralized digital information system, particularly a website that can serve as an integrated platform for disseminating school information. Currently, the school relies on several social media platforms to distribute information, which requires additional time and effort for information management and communication with the public. This study developed a website for SMK Suarna Wisata Tes to facilitate the delivery and dissemination of school-related information. The digitalization of the school information system provides several benefits. Information related to teachers, students, and school profiles can be centrally stored and made accessible to the wider community. In addition, all school announcements and news can be managed in an integrated, efficient, and persistent manner. The website development implemented the Design Thinking method, which focuses on user-centered needs within the school environment. The implementation results demonstrated a positive impact on SMK Suarna Wisata Tes. Information dissemination became faster, more accurate, and more accessible to the broader community. Furthermore, data could be stored digitally and managed more efficiently. The findings of this study can serve as a reference model for the education sector in designing digital systems for schools located in border regions.